ANALYSIS OF GENERATION Z CONSUMER PREFERENCES AT COFFEE SHOPS IN BANJARMASIN CITY - Yarna Hasiani; Fuzi Maulana Ash'ari; Tota Totor Naibaho (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
Coffee is a widely consumed beverage across all demographic groups, and coffee shops represent a vital downstream component of the agribusiness subsystem, particularly in the marketing of plantation products in ready-to-serve or ready-to-eat formats within the food and beverage industry. This study aims to analyze the selection preferences of Generation Z consumers in choosing coffee shops in the city of Banjarmasin. Utilizing conjoint analysis, the research identifies the relative importance of various attributes influencing consumer decision-making. The most influential factor is Sales Product, with an interest level of 23.003, followed by price (21.839), facilities (20.774), building concept (14.532), trademark (10.389), and location (9.462). These findings suggest that Generation Z places higher value on product offerings and affordability when selecting coffee shops, while branding and location play lesser roles. This information provides strategic insights for coffee shop entrepreneurs targeting this consumer segment in urban Indonesia.